Integrating Character Education Into the RECE Learning Model Through Pancasila and Citizenship Education Subjects - Sarkadi; Casmana, Asep Rudi; Hisyam, Ciek Julyati; Wardatussa'idah, Indah (Frontiers in Education, 2022)
The Ministry of Education and Culture is currently developing Strengthening Character Education (PPK) through learning in the classroom, in the family and in the community. This KDP will be successful when the three components are in synergy. Problems arise when there are differences between schools, families and communities in implementing them. The difference in application will make the child confused about which one to follow. Is character education received at school, in the family or in the community. Character education is not actually taught in class. The purpose of this research is to provide convenience for Civics teachers when implementing character education for students. By applying the study of the RECE learning model, it is hoped that students will be able to reflect, connect, collaborate, and be able to communicate well. In the first year the researcher used a questionnaire to obtain data on the study of learning models conducted on teachers in several high schools in the DKI Jakarta area. In the second year the research was continued by finalizing the study of the model that had been obtained in the first year by conducting several trials in several high school schools in DKI Jakarta. The end result is the study of the RECE learning model that is integrated with character education. In the third year, the results of the study of the RECE learning model that have been produced are implemented in schools. The effectiveness of the study of the implemented RECE learning model is monitored by a learning implementation questionnaire.